IMPLEMENTASI LITERASI AL-QURAN DALAM MENINGKATKAN KUALITAS BACAAN MELALUI KEGIATAN TAHSIN DI SMK TRITECH - Syafira Ayu Armadhy Putri; Zailani (AT-TA'DIB: JURNAL ILMIAH PRODI PENDIDIKAN AGAMA ISLAM, 2023)
This research focuses on implementing Al-Qur'an literacy, especially through tahsin activities, to improve the quality of Al-Qur'an reading at Tritech Vocational School. The aim is to evaluate the impact of the tahsin method on students' ability to read the Koran. By using a subjective approach, data was obtained through meetings, perceptions, and documentation from teachers as subjects and students as research objects. The results show that the application of the tahsin method is successful in improving Al-Qur'an reading skills, with supporting factors involving student readiness, quality of educators, learning intentions, and learning objectives. However, obstacles such as lack of control by educators and students' laziness need to be considered. In conclusion, the implementation of the tahsin method at Tritech Vocational School is effective in improving the quality of Al-Qur'an reading, and the evaluation provides input for improving teaching strategies and the role of parents in supporting Al-Qur'an learning.